The Effect of Picture and Picture Learning Model on Learning Outcomes of IPAS Subjects of Fourth Grade Students in SDN 3 Rajabasa Bandar Lampung - Fajariah, Marisa; Herpratiwi, Herpratiwi; Pamungkas, Arimbi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
This study was motivated by the problem of low student learning outcomes, lack of student interest in learning and the lack of teachers in utilizing learning models. The research was conducted at SD Negeri 3 Rajabasa Bandar Lampung with a research focus on class IV. The aim of the research is to analyze whether or not there is an influence if applying the Picture and Picture learning model to students of SD Negeri 3 Rajabasa Bandar Lampung. The sampling technique in this study used random sampling. The method used in this study is an experiment with a type of quantitative research and the design used is one group pre-test and post-test. The data collection technique used in this study was to use a test. The results of this study based on hypothesis testing using paired t test, namely, obtained tcount = 3.522 at a significant level of 5% which is 1.761. Thus, tcount> ttable (3.522> 1.761). Based on the results of the hypothesis, Ha is accepted and H0 is rejected, meaning that there is an effect of the application of the Picture and Picture learning model on student learning outcomes in Natural and Social Sciences subjects in grade IV students of SD Negeri 3 Rajabasa.